2018
DOI: 10.1016/j.biortech.2018.03.116
|View full text |Cite
|
Sign up to set email alerts
|

Environmentally persistent free radicals mediated removal of Cr(VI) from highly saline water by corn straw biochars

Abstract: Heavy metal ions coexisting with salts in the contaminant water are difficult to remove due to the interference of salts. Herein, biochars were pyrolyzed by corn straw at different temperatures, aiming to remove Cr(VI) in the presence of salts. Results show that biochars had surprisingly selective adsorption of Cr(VI). X-ray photoelectron and X-ray absorption near edge spectra revealed that Cr(VI) was reduced to Cr(III). All the adsorption was conducted at pH ∼ 7, which differed from the previous studies that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
38
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 148 publications
(45 citation statements)
references
References 47 publications
1
38
0
Order By: Relevance
“…The abundance of carbon-centered persistent free radicals (PFRs) on carbonaceous materials can act as excellent reductants for pollutants and H 2 O 2 activation (Ruan et al, 2019;Qin et al, 2018;Yang et al, 2016;Yu et al, 2019;Zhao et al, 2018;Zhong et al, 2018). Recently, Qin et al (2017) demonstrated that PFRs on hydrothermal carbon could act as an electron donor and favor electron transfer from surface hydroxyl groups to Fe(III) to promote Fe(III)/Fe(II) cycling.…”
Section: Cr(vi) Reduction Mechanism With Mgbsmentioning
confidence: 99%
“…The abundance of carbon-centered persistent free radicals (PFRs) on carbonaceous materials can act as excellent reductants for pollutants and H 2 O 2 activation (Ruan et al, 2019;Qin et al, 2018;Yang et al, 2016;Yu et al, 2019;Zhao et al, 2018;Zhong et al, 2018). Recently, Qin et al (2017) demonstrated that PFRs on hydrothermal carbon could act as an electron donor and favor electron transfer from surface hydroxyl groups to Fe(III) to promote Fe(III)/Fe(II) cycling.…”
Section: Cr(vi) Reduction Mechanism With Mgbsmentioning
confidence: 99%
“…Many biochars derived from different biomass (agriculture waste, sewage sludge, wood waste, etc.) have been used as absorbents for Cr(VI) removal from aqueous solution and were found to have favorable properties for applications [8,9]. However, various feedstock biochars showed huge differences in adsorption capacity, due to the differences in the properties of the biochars [10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the corn straw-derived biochar showed higher efficiency for the removal of Cr(VI) by reduction into Cr(III) compared to other biochar materials. Zhao et al [31] carried out the saline water-mediated Cr(VI) removal by biochar synthesized with corn straw biomass pyrolyzed at different temperatures (300, 500, and 700 • C) to examine the influence of the biochar surface according to the pyrolysis temperature. The removal of Cr(VI) decreased significantly with increasing the pyrolysis temperature because of decreasing the number of oxygenated functional groups, such as hydroxyl or carbonyl groups, which transfer electrons to Cr(VI).…”
Section: Removal Of Environmental Pollutantsmentioning
confidence: 99%